EVALUATION OF THE EFFECTIVENESS OF SACCHAROMYCES BOULARDII IN CHILDREN WITH ACUTE INFECTIOUS DIARRHEA - Ashurova Sanam Bakhtiyor qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the evaluation of the effectiveness of S. boulardii (CNCMI-745 strain) in the complex treatment of children with acute infectious diarrhea still the age of 5 years. Due to its biological properties, this drug acts on a wide range of pathogenic and opportunistic bacteria, suppressing the ability of bacteria to produce toxins and neutralizing them, strengthening protection against non-specific infection. Reason is a complex of enzymes (lactase, maltase, etc.), it significantly regulates and stimulates digestion, promotes better assimilation of food.